Implementation of Appropriate Technology for Durian Peel Waste Extractor in Rowosari Village to Realise An Independent Village for Green Economy - Kamiliah, Thiflatul; Taufiqurrohman, Muhammad; Arkan, Naufal; Brilianto, Mochamad Syadam; Alfarizi, Muhammad Alfian; Ahmad Reza Maulufi; Septiana, Windi Yudita; Syawaludin, Syafriel Razaan; Saputra, Dicky Aditya; Nurkholisah, Siti; Setiawan, Felix Arie; Rahmawati, Istiqomah (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2025)
The University of Jember's Student Village Program (Promahadesa) was implemented in Pringpadhu Hamlet, Rowosari Village, Sumberjambe District, Jember Regency, with the aim of overcoming the problem of durian peel waste that has not been utilized and causes environmental pollution. This activity aims to process the waste into products of economic value through the application of appropriate technology tools (TTG) in the form of extractors. The method used in this activity is Participatory Action Research (PAR), which involves the community actively in all stages of the activity, from problem identification, planning, implementation, to evaluation. The implementation of activities includes: design and assembly of household scale extractor tools, pretreatment of durian skin waste, the process of making dish soap and liquid organic fertilizer (POC), as well as socialization and demonstration of tools to the community. The results of this activity are the creation of TTG extractor tools and two main processed products, namely dish soap and POC, which are produced from durian skin distillate. The conclusion of this activity shows that the application of technology can increase community knowledge, minimize environmental pollution, and potentially add local economic value through the utilization of waste into village superior products.